IMPLEMENTASI PESERTA ECONOMY SOCIAL CARE UNTUK MENINGKATKAN PEMAHAMAN MAGGOT FARMING SEBAGAI ALTERNATIF PENGELOLAAN SAMPAH DAN PENGATURAN EKONOMI LOKAL BERBASIS SDGs - Made Natalia Cahyani; Ni Luh Putu Herlina; Dewa Gede CandraWiraguna; I Gusti Ngurah Erlangga Bayu Rahmanda Putra (JURNAL PENGABDIAN MANDIRI, 2026)
This study aims to examine the implementation of the Economy Social Care (ESC) Program in improving participants' understanding of the maggot farming program as an alternative waste management and strengthening the local economy in line with the Sustainable Development Goals (SDGs). The ESC program is a community service activity that emphasizes the introduction of community-based circular economy innovations through Black Soldier Fly (BSF) maggot cultivation. This study used a qualitative approach with a reflective case study method involving 50 ESC participants as research subjects. Data collection techniques were carried out through reflective questionnaires, field observations, and in-depth interviews. The results showed that participants' direct involvement in maggot farming practices was able to improve their understanding of sustainable organic waste management and open insights into the economic potential of maggot cultivation. In addition, this program also fostered environmental awareness and interest in social entrepreneurship among participants. The implementation of the maggot farming program in ESC contributes to the achievement of the SDGs, particularly in the aspects of responsible consumption and production and strengthening the SDG-based economy.